Upper airways modelling and validation of mandibular advancement surgery - Nik Ghazali, Nik Nazri; Badruddin, Irfan Anjum; Abdul Latif, Mohd Faruq; Abdullah, Mohd Faris; Ibrahim, Norliza; Mohd Razi, Roziana; Tuan Ya, Tuan Mohammad Yusoff Shah; Badruddin, Irfan Anjum; Kamangar, Sarfaraz; Zedan, ASA; Khan, Abdul Azeem (SAGE Publications Ltd, 2025)
Background: Most Obstructive Sleep Apnoea (OSA) treatments use cross-sectional examination of the Upper Airways (UA) to determine decreasing gap and UA length. Surgery is detrimental to all OSA patients, stressing the need for better assessment. Objective: This study integrates Computational Fluid Dynamics (CFD) with physical model validation to improve OSA prediction and turbulence model accuracy and dependability. Methods: The k-omega SST turbulence model is used to analyse OSA using CFD. SLS is used to build a physical model of the UA for CFD simulations. The UA’s physical model is then compared to the OSA-recommended CFD turbulence model to verify simulation-physical reality coherence. Result: The average UA pressure differential decreases considerably after mandibular advancement surgery. The Turbulent Kinetic Energy (TKE) increases after surgery, indicating more turbulence. Cross-validation of the physical model confirms the OSA CFD turbulence simulation’s validity. Conclusion: The study concludes that matching UA simulations with physical models improves OSA assessments. CFD with established physical models is a reliable method for assessing OSA therapy, especially surgical operations. The post-surgery increase in TKE needs more study to determine its effects on OSA treatment outcomes.